Nonhuman treatment reduces helping others: self-dehumanization as a mechanism - Zhang, Zaixuan; Chen, Zhansheng (Frontiers in Psychology, 2024)
Objectification is a daily experience with various negative consequences. In four studies (N = 877), we tested whether and how objectification experience contributes to decreased prosociality. Using correlational designs (Studies 1 and 2), we found that participants’ objectification experience negatively predicted their prosocial intention and that self-dehumanization could account for the negative association between objectification and prosocial intention. Next, by manipulating participants’ objectification experience, we found the negative effect of objectification on prosocial intention, as well as the mediating role of self-dehumanization (Studies 3 and 4). Additionally, we tested the mediating role of self-dehumanization in comparison with relative deprivation (another potential mediator), and consistently found that self-dehumanization was a stronger mediator in accounting for the effect of objectification on prosocial intention (Studies 1, 2, and 4). Together, our findings support the process of self-dehumanization following objectification and offer new insights into the relationship between objectification and prosociality. The implications and limitations of the research were discussed.